PUBLIC SERVICE QUALITY AS AN INFORMAL INSTRUMENT OF POLITICAL EDUCATION: IMPLICATIONS FOR PUBLIC INSTITUTIONAL TRUST - Enjang Kusnadi (PT. Radja Intercontinental Publishing, 2026)
Abstract Political education in Indonesia is often reduced to electoral participation, ignoring the crucial role of citizens' daily interactions with the bureaucracy. This study aims to analyze how the quality of administrative services transforms into an informal political education tool that affects the level of institutional trust at the local level. Employing a descriptive qualitative approach through a case study in Cimaja Village, Sukabumi Regency, data were collected using a rapid assessment technique consisting of observations and in-depth interviews with residents and village apparatus. The results show that responsive, equal, and transparent public services by street-level bureaucracy empirically function as a democratic